Changes in vinegar quality and microbial dynamics during fermentation using a self-designed drum-type bioreactor - Wang, Wenxiu; Zhang, Fan; Dai, Xinpeng; Liu, Yaqiong; Mu, Jianlou; Wang, Jie; Ma, Qianyun; Sun, Jianfeng (Frontiers in Nutrition, 2023)
The bioreactor based on solid-state fermentation technology has been developed for vinegar production, standardization of fermentation process and stabilization of vinegar quality. The microbial community diversity, and volatile compounds of six cultivars of vinegar samples fermented in a self-designed solid-state fermentation bioreactor were investigated using Illumina MiSeq platform and gas chromatography mass spectrometry (GC-MS) technology. The correlations between the richness and diversity of microbiota and volatile profiles, organic acids, as well as physicochemical indicators were explored by R software with the coplot package. The findings indicated that Acetobacter, norank-c-Cyanobacteria, and Weissella played key roles during fermentation process. Norank-f-Actinopolyporaceae, norank-c-Cyanobacteria, Pediococcus, and Microbacterium had significant correlations with the physicochemical characteristics. The most common bacterial species were associated with citric acid content, whereas the least number of bacterial species correlated with malic acid content. The findings could be helpful for the bioreactor optimization, and thus reaching the level of pilot scale and industrialization.